Nexus between financial stability and earning management in company competitiveness - Utami, Elok Sri; Amelia, Tiara (International Journal of Management and Sustainability, 2024)
This research investigates financial stability with earnings management practices in the normal economic time dimension, the COVID-19 crisis period, and the recovery period, as a form of competitiveness. Earnings management (EM) in research is classified into high, medium, and low, and financial stability is divided into non-financial distress, gray zone and financial distress. We classify Earnings management (EM) into high, medium, and low and further categorize financial stability into non-financial distress, gray zone, and financial distress. The purposive sampling method generates a total of 141 manufacturing sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The study employed the cross-tab method for analyzing the relationship between financial stability and earnings management. The classification of financial stability was measured using the Altman Z-score category, while the measurement of earnings management was measured using the DeAngelo model and the Modified Jones Model. The results show that there is a relationship between financial stability and earnings management, where non-financial distress companies and gray zone ones perform negative (high) earnings management, presumably because they have greater opportunities to carry out the accounting numbers of companies that are financially distressed. During non-crisis or normal times, companies classified as non-financial distress, gray zone, and financial distress engage in positive earnings management, especially non-financial distress companies.